2009
DOI: 10.1016/j.neuroimage.2009.01.016
|View full text |Cite|
|
Sign up to set email alerts
|

Tuning down the emotional brain: An fMRI study of the effects of cognitive load on the processing of affective images

Abstract: a b s t r a c t a r t i c l e i n f oThe present research examines whether cognitive load can modulate the processing of negative emotional stimuli, even after negative stimuli have already activated emotional centers of the brain. In a functional magnetic resonance imaging (fMRI) study, participants viewed neutral and negative stimuli that were followed by an attention-demanding arithmetic task. As expected, exposure to negative stimuli led to increased activation in emotional regions (the amygdalae and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
167
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(196 citation statements)
references
References 48 publications
20
167
3
Order By: Relevance
“…As a result, PTSD may 13 result in an interplay between enhanced "emotional" processing networks that serve to enhance 14 attention towards specific stimuli, and decreased "inhibitory" networks meant to disengage 15 attention and redirect it to the task at hand (Aupperle et al, 2016). Moreover, evidence showed 16 that attentional biases may maintain PTSD symptoms, impede information processing, and disrupt 17 cognitive abilities (Weber, 2008). 18 However, it is not completely clear whether attentional bias in PTSD varies as a function of 19 emotional content (i.e., trauma-related or trauma-unrelated stimuli).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, PTSD may 13 result in an interplay between enhanced "emotional" processing networks that serve to enhance 14 attention towards specific stimuli, and decreased "inhibitory" networks meant to disengage 15 attention and redirect it to the task at hand (Aupperle et al, 2016). Moreover, evidence showed 16 that attentional biases may maintain PTSD symptoms, impede information processing, and disrupt 17 cognitive abilities (Weber, 2008). 18 However, it is not completely clear whether attentional bias in PTSD varies as a function of 19 emotional content (i.e., trauma-related or trauma-unrelated stimuli).…”
mentioning
confidence: 99%
“…In this context, the goal of the present study was twofold: (i) we 17 intended to identify the presence of a deficit in cognitive control among individuals with PTSD, 18 and if so, (ii) further examine whether any such deficit may vary as a function of stimulus type…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have also shown that activation of the DLPFC in the context of difficult cognitive tasks can reduce the neural response to emotional stimuli. Van Dillen and colleagues (Van Dillen, Heslenfeld, & Koole, 2009) required participants to view neutral and aversive International Affective Picture System (IAPS) pictures (Lang, Bradley, & Cuthbert 2005); following picture offset, participants performed complex or simple math. High-load math problems resulted in greater activation in the DLPFC and were associated with reduced ratings of negative affect and decreased amygdala and insula activity in response to aversive pictures.…”
mentioning
confidence: 99%
“…Accordingly, the left superior frontal gyrus has also been found to be overactivated by sexually abused women with PTSD during retrieval of emotional compared with nonemotional items, with no amygdala activity increases. 30 Moreover, van Dillen and colleagues 31 have demonstrated less amygdala activation due to trauma-related material when a cognitive task was used, potentially indicating a downregulation of dorsal cognitive activations on ventral emotional structures. Increased activations of left dorsal frontal areas on trauma-related contrasts during cognitively demanding tasks along with the absence of trauma-related performance decreases in patients with PTSD are broadly consistent with these results, indicating potential compensatory processes in trauma-related cognition.…”
mentioning
confidence: 99%